Portable anti forgery recognition for attendance system using fingerprint based biometric - Zainal, Nur Izzati; Sidek, Khairul Azami; Gunawan, Teddy Surya (Asian Research Publishing Network (ARPN), 2016)
In this paper, a portable anti forgery recognition for attendance system using fingerprint based biometric is presented. Portability and security are the main purpose of applying biometric characteristics in a portable attendance system. An independent energy source and its miniature design make the system more efficient in terms of the portability criterion. This study introduces a system which overcomes the limitations of existing paper based attendance method and queuing delays due to fixed fingerprint reader installed in front of class entrances. Furthermore, in terms of security, encryption has been implemented to preserve data integrity. Results of the study include several analysis which among others involved student perceptions, average time taken and classification accuracy of biometric recognition. Moreover, a comparison study was done using the proposed and paper based methods.